1890-ական թթ. հայկական կոտորածների արձագանքները «Մուրճ» պարբերականում - Լ. Ս. Քոսյան (ՀՀ ԳԱԱ հրատ.)
На страницах журнала “Мурч” было издано множество м атериалов,посвященных армянским погромам 1890-ых гг. Опубликованные в “Мурче” фактические материалы являют собой огромную ценность, поскольку они воссоздают объективную картину потерь армянского на селения, в частности, Харбердской губернии и 59 деревень. Armenian periodicals comprise a lot of documents an d materials about the Armenian massacres. “Murch” magazine, initiated by Avetis Araskhanyan in Tiflis,covered Sasoun massacres, the ensuing peaceful protests and barbaric acts during those demonstrations, the reaction of European countries, May reforms and the massacres that started in 1895. There is also detailed information about the Armenian massacres in Kharberd region and its 59 villages (1 October,1895 – 15 January,1896). The appendix of the article comprises the list of destroyed villages in Sasoun.
Keywords: History; General Works; D History; AMS Armenian Massacres; Պարբերական